External Validation of Cochlear Implant Screening Tools Demonstrates Modest Generalizability. Issue 9 (1st October 2022) - Lee, David S.; Herzog, Jacques A.; Walia, Amit; Firszt, Jill B.; Zhan, Kevin Y.; Durakovic, Nedim; Wick, Cameron C.; Buchman, Craig A.; Shew, Matthew A.
Abstract : Objective: To assess the clinical application of five recently published cochlear implant (CI) candidacy evaluation (CICE) referral screening tools through external validation. Study Design: Retrospective cohort study. Setting: Tertiary otology/neurotology practice. Patients: Adults who underwent CICE between December 2020 and September 2021. Intervention(s): CICE referral screening tools versus CI candidacy criteria. Main Outcome Measure(s): CICE screening tool performance, based on the ability to identify patients who met the CI candidacy criteria, was evaluated. CI candidacy criteria were defined as best-aided AzBio sentences at +10 signal-to-noise ratio and either 60% or less accuracy to reflect traditional criteria used in clinical settings or 40% or less accuracy (only patients 65 years or older) to reflect Medicare-eligible criteria. Results: Screening criteria of proposed CICE referral tools vary widely across pure-tone average and word recognition scores. When screened by traditional criteria, the sensitivities and specificities of these referral tools varied from 40 to 77% and from 22 to 86%, respectively. When screened by Medicare-eligible criteria, sensitivities and specificities varied from 41 to 81% and from 24 to 91%, respectively. The screening tool proposed by Zwolan et al. ( Otol Neurotol 2020;41(7):895–900) demonstrated the best overall performance for traditional (Youden's J, 0.37; sensitivity, 62%; specificity, 75%) and Medicare-eligible patients (Youden's J, 0.44; sensitivity, 66%; specificity, 78%). All screening tools performed worse on the validation cohort compared with their respective development cohorts. Conclusions: Current tools for determining CICE referral have diverse screening criteria. These combinations of pure-tone average and word recognition score are modestly successful at identifying CI candidates.